Effect of a calcium hydroxide-based intracanal medicament containing N-2-methyl pyrrolidone as a vehicle against Enterococcus faecalis biofilm (Journal of Applied Oral Science, 2021)
This study investigated the effect of a calcium hydroxide (CH) paste (CleaniCal®) containing N-2-methyl pyrrolidone (NMP) as a vehicle on Enterococcus faecalis (E. faecalis) biofilms compared with other products containing saline (Calasept Plus™) or propylene glycol (PG) (Calcipex II®). Methodology: Standardized bovine root canal specimens were used. The antibacterial effects were measured by colony-forming unit counting. The thickness of bacterial microcolonies and exopolysaccharides was assessed using confocal laser scanning microscopy. Morphological features of the biofilms were observed using field-emission scanning electron microscopy (FE-SEM). Bovine tooth blocks covered with nail polish were immersed into the vehicles and dispelling was observed. The data were analyzed using one-way analysis of variance and Tukey tests (p<0.05). Results: CleaniCal® showed the highest antibacterial activity, followed by Calcipex II® (p<0.05). Moreover, NMP showed a higher antibacterial effect compared with PG (p<0.05). The thickness of bacteria and EPS in the CleaniCal® group was significantly lower than that of other materials tested (p<0.05). FE-SEM images showed the specimens treated with Calasept Plus™ were covered with biofilms, whereas the specimens treated with other medicaments were not. Notably, the specimen treated with CleaniCal® was cleaner than the one treated with Calcipex II®. Furthermore, the nail polish on the bovine tooth block immersed in NMP was completely dispelled. Conclusions: CleaniCal® performed better than Calasept Plus™ and Calcipex II® in the removal efficacy of E. faecalis biofilms. The results suggest the effect might be due to the potent dissolving effect of NMP on organic substances.